STUDI KINERJA HANDHELD PORTABLE 3D SCANNER DALAM PENGUKURAN DIAMETER DAN KEDALAMAN LUBANG PADA SPESIMEN LOGAM - Anang Wahyu Setiawan; Muslimin Muslimin; Ghany Heryana (P3M Politeknik Negeri Indramayu, 2023)
A Handheld portable 3D Scanner is an optical-based tool that can be gripped by hand and moved from one place to another. This tool is used to scan part’s surface and produce a 3-dimensional representation in the form of a point cloud. The use of 3D Scanners has grown significantly in recent years, especially in applications in the metrology, industrial manufacturing inspection, and reverse engineering. Apart from the ease of use and flexibility of use, as an optical-based tool with triangulation principles, Handheld Portable 3D Scanners have limitations in scanning the geometric shape of a narrow hole or slit. The specifications published by the manufacturer do not fully describe tool’s performance in this regard. For this reason, an evaluation of the performance of the Handheld Portable 3D Scanner is carried out by determining the error of measuring holes on the workpiece with variations in depth and diameter. As a reference value, the results of the Coordinate Measuring Machine –CMM measurement are used. . The study result show that handheld 3D scanners generally have an error in measuring the diameter and measuring the depth of the hole, above the specification of 0.03 mm. In holes with a diameter of 1 mm, the handheld 3D scanner has a relationship between the error of measuring hole’s diameter and hole’s diameter with the regression equation: y=0.037x-0.54. En values categorized as